A COMPARATIVE STUDY ON THE EFFECTS OF TAI CHI AND MATTER OF BALANCE ON MEASURES OF BALANCE AND FALL EFFICACY IN OLDER ADULTS - Burgess, Lacey A. (East Carolina University, 2012)
The purpose of this study was to compare the effectiveness of two intervention strategies, Tai Chi (n = 12) and Matter of Balance (n = 13) on balance and fall efficacy of adults 65 years and older as compared to a control group (n = 12). The study compared changes in balance and fall efficacy of the two strategies in an effort to design a more robust fall reduction program for future application. Participants were assessed via pre-test-post-test eight to ten weeks apart by means of two balance tests: the 8-foot Up and Go (UG) test and the Multi-Directional Reach Test (MDRT); as well as a fall efficacy questionnaire: Activities-specific Balance Confidence (ABC) Scale. Results from this study indicate that TC and MOB were both effective in improving or maintaining balance and fall efficacy as compared to the control group. Results show trends leaning toward TC as having a greater impact on participants' overall balance.
Keywords: Gerontology; Balance; Fall efficacy; Interventions; Older adults; Tai chi; Equilibrium (Physiology); Falls (Accidents) in old age; Exercise for older people; Tai chi for older people; Matter of Balance